La perte en filigrane Cet imperceptible mouvement d’Aude - Kapołka, Karolina (Romanica Silesiana)
Considered one of the most interesting Quebec writers, Aude released a collection of short stories entitled Cet imperceptible mouvement in 1997. What comes to the fore in that collection is the austerity of style intertwined with a unique emotional load, a combination which has raised critics’ eyebrows even if it is typical of Aude’s prose. One of the pivots of her stories is the notion of loss, looked at from various angles. The protagonists typically lose their dearest ones, be it because the latter leave, die or because they drown in mourning. Maimed with the loss, the protagonist reassesses his/her life, faces new challenges, makes constant choices. Excelling in the short story structure, Aude records the depth of loneliness and raises existential queries by means of what might at first sight seem simple gestures, common objects and insignificant situations. Key words: Aude, short story, transformation, loss, death.